Effect of Crushed Eruca sativa Seeds Supplementation to Quail Ration on Lipid Profile Before and After Sexual Maturity - Abdullah Abdul-Majeed; Sarmad Hashem Taha (Mesopotamia Journal of Agriculture)
The study aimed to evaluate the effect of crushed Rocket salad (Eruca sativa) seeds on serum lipid profile and risk index of males and females quail before and after sexual maturity. A total of two hundred forty unsexed quail (Coturnix coturnix) (7 days aged) were randomly distributed into 4 groups (60 birds/ group,   5 replicates, 12 birds / replicate), the feed and water were allowed ad libitum, and the treatment continued till 77 days age, as follows:- 1st group(control): birds were reared on standard ration (without Eruca sativa seeds) 2nd group: birds were reared on standard ration supplemented with 6 g / kg crushed Eruca sativa seeds from the age of 7 days till 42 days age. 3rd group: birds were reared on standard ration supplemented with 6 g / kg crushed Eruca sativa seeds from the age of 42 days till 77 days age. 4th group: birds were reared on standard ration supplemented with 6 g / kg crushed Eruca sativa seeds for the whole period of experiment (7 - 77 days). The addition of crushed Eruca sativa seed don't change the level of blood glucose, but it improves serum lipid profile in males and females quail, especially when given in the early stage of growth before sexual  maturity (Eruca sativa from 7days age), and there was a significant decrease (P≤0.05) in the level of cholesterol, triglycerides and VLDL-C compared with control. Also the addition of Eruca sativa seeds in the ration enhanced and significantly increased (P ≤ 0.05) the level of HDL-C in males and females quail before sexual maturity (2nd and 4th groups), and there is no significant changes in the level of LDL-C compared with control, which reflected in improvement of risk index (LDL/HDL) especially when Eruca sativa seeds were added from 7 days age. On the other hand, the addition of Eruca sativa seeds reduced the stress effects in males and females quail as represented by a significant decrease (P ≤ 0.05) in  AST and ALT values as compared with the control group. In conclusion, the addition of crushed Eruca sativa seeds improve the lipid profile and risk index, also reduce stress condition in males and females quail, especially when given in the growth stage and  before sexual maturity.